2008
DOI: 10.1016/j.ajog.2007.12.028
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of vessel maturation on antiangiogenic therapy in ovarian cancer

Abstract: Condensation-Pericytes contribute to endothelial survival in tumor vasculature and represent a potential therapeutic target.Objective-To examine the functional and therapeutic significance of pericytes in ovarian cancer vasculature.Study Design-Tumor vessel morphology and efficacy of endothelial and pericyte targeting were examined using in vivo ovarian cancer models. The expression of platelet derived growth factor (PDGF) ligands and receptors was examined in endothelial, pericyte-like, and ovarian cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 32 publications
4
41
0
Order By: Relevance
“…Similar normalized revascularization was observed in the H441 orthotopic model (Figures 7 and 8). Prior studies have indicated that pericyte coverage may exert a protective effect on tumor endothelium (66,67), potentially through the production of factors promoting endothelial survival and VEGF independence. Our findings were consistent with this hypothesis and revealed pericyte EGFR signaling to be a potential mediator of this effect.…”
Section: Figurementioning
confidence: 99%
“…Similar normalized revascularization was observed in the H441 orthotopic model (Figures 7 and 8). Prior studies have indicated that pericyte coverage may exert a protective effect on tumor endothelium (66,67), potentially through the production of factors promoting endothelial survival and VEGF independence. Our findings were consistent with this hypothesis and revealed pericyte EGFR signaling to be a potential mediator of this effect.…”
Section: Figurementioning
confidence: 99%
“…The FGF family activates angiogenesis via interaction with FGF receptors 1 and 2 [33]. It is thought that signaling via these alternate pathways (PDGF, FGF) may mediate resistance to VEGF inhibition, supporting a multi-targeted approach [34][35][36][37][38]. In response to receptor-ligand binding, downstream signaling pathways, PI3K-Akt-mTOR and Ras-MEK-Erk, are activated and have been identified as potential targets for drug development [39,40].…”
Section: Targeting Angiogenesis Pathwaysmentioning
confidence: 99%
“…10B in the Supplementary Appendix). 18,23 Platelet depletion with the use of antiplatelet antibody, as compared with control IgG, resulted in an increase in tumorcell and endothelial-cell apoptosis by a factor of four and a factor of eight, respectively (P = 0.008 and P<0.001, respectively) ( Fig. 10C in the Supplementary Appendix).…”
Section: Biologic Significance Of Paraneoplastic Thrombocytosismentioning
confidence: 99%
“…16,17 Dual immunofluorescence staining for CD31 and desmin and for CD31 and terminal deoxynucleotidyl transferase dUTP biotin nick end labeling (TUNEL) was used to assess pericyte coverage and apoptotic tumor and endothelial cells, respectively. 18 The in vitro effects of gel-filtered platelets (see the Supplementary Appendix) on cell migration and proliferation in epithelial ovarian cancer were evaluated with the use of two-chamber chemotaxis and bromodeoxyuridine flow-cytometric assays (Click-iT EdU, Invitrogen), respectively. 19…”
Section: Laboratory Measuresmentioning
confidence: 99%